LOGISTICS AND GEOGRAPHY OF CRUISE TOURISM: THEORY AND PRACTICE OF RESEARCHES - Смирнов, Ігор (Human Geography Journal, 2014)
Revealed the conceptual framework and practical features of Logistics and Supply Chain Management in cruise tourism as a source of competitive advantage in the global cruise market. Proposed supply chains complexity concept in the cruise business, which is based on three components: the theory of logistics strategies by A. Bask, model of flexible supply chains by M. Nime and P. Kralich’s matrix that specifies the structure of the supply chain that is needed to ensure its flexibility and to implement effective sourcing strategy